Fluoride removal in drinking water using activated carbon prepared from palmyrah (Borassus flabellifer) nut shells - Senewirathna, D.S.G.D.; Suganja, T.; Prabagar, S.; Prabagar, J. (Elsevier, 2022)
Fluoride is a useful ion for human health and fluoride related health problems can occur due to the deficiency or excess intake. Human intake of fluoride is consumed mainly from drinking water. The removal of fluoride ions from its aqueous solutions and water samples using activated carbon, was conducted in this study. For the preparation of activated carbon dried palmyrah (Borassus flabellifer) nut shells were used as a low cost adsorbent. Activation of dried palmyrah nut shell charcoal was done with concentrated H3PO4 and 25% NaOH separately as activating agents. Characterization of the non-activated carbon (NAC), phosphoric acid activated carbon (PAC) and sodium hydroxide activated carbon (SHAC) was conducted using different parameters. Fluoride removal efficiency of PAC was investigated for a synthesized fluoride solution which was prepared using NaF and deionized water in four different conditions such as contact time, adsorbent dosage, initial fluoride concentration and temperature. Fluoride concentration in samples was measured by SPADNS method. Then seven different field water samples were collected from Nochchiyagama area, Anuradhapura district which is a major fluoride contaminated ground water containing area in Sri Lanka. The physicochemical characteristics of PAC was found to be high compared to NAC and SHAC. Optimum conditions for the highest fluoride removal efficiency of PAC were observed as 45 min contact time, 0.2g adsorbent dosage, 1 mg/L initial fluoride concentration at 30 C temperature with 61% adsorption efficiency. The pseudo-first order and pseudo second order kinetic models were applied in this experiment. The pseudo second order exhibited the best fit for the kinetics studies that indicates the chemisorption process. The experimental isotherm data were analysed by different models; the adsorption follows the Freundlich model providing better fit for the equilibrium data. PAC from palmyrah nut shells would make an alternative source of activated carbon and low cost adsorbent for the fluoride ions.
Keywords: Fluoride removal; Adsorption; Kinetics; Isotherm; Palmyrah nut shell activated carbon